Sustainable skills for the world of work in the digital age - Sousa, M.; Daniela Wilks (Systems Research and Behavioral Science, 2018)
The skills that small and medium-sized enterprises will need in the near future are an essential research topic that has not yet been appropriately addressed. The current paper aims to fill this gap in the literature. Explicitly, the study aimed to identify the critical skills for organizations and the disruptive technological skills. To this end, a literature review was conducted, and an online survey explored the main critical skills for the future and the disruptive technological skills contributing to achieving sustainable employability. The critical skills identified in the study were complex problem-solving, critical thinking, creativity, people management, coordinating with others, emotional intelligence, judgement and decision making, service orientation and negotiating and cognitive flexibility. As for the disruptive technological skills, these were artificial intelligence, nanotechnology, robotization, internet of things, augmented reality and digitalization. Findings may assist companies to develop the skills needed to respond to the challenges of a continuously changing business environment.